Gastric volvulus and giant Bochdalek hernia in an adult patient that were safely repaired by endoscopic reduction and elective laparoscopic surgery. Issue 1 (2nd June 2020) - An, Byonggu; Zen, Yumi; Akabori, Hiroya; Kitamura, Naomi; Ohta, Hiroyuki; Otsuki, Akinori; Mizuta, Hiroo; Tsujikawa, Tomoyuki; Mekata, Eiji
Abstract: A Bochdalek hernia (BH) is a congenital abnormality with incomplete closure of the diaphragm. It is usually manifested in infants but rarely in adults. Here, we report an adult patient with gastric volvulus and giant BH that were safely repaired by endoscopic reduction and elective laparoscopic surgery, respectively. A 79‐year‐old woman presented with left upper abdominal pain but no history of trauma. CT revealed a giant BH with gastric volvulus. After emergency endoscopic reduction of the volvulus, elective laparoscopic repair of the BH was performed. The 8 × 8‐cm defect was repaired with interrupted nonabsorbable sutures and a mesh. The patient's postoperative course was uneventful, and no complications or recurrence were observed in the 6 months that followed.